Isolation of Cellulolytic Bacteria from Oyster Mushroom Baglog Compost - Lolita Endang Susilowati; Kurnia, Sandra Cahya; Jaya, Dori Kusuma (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Oyster mushroom baglog compost is an organic waste rich in cellulose, making it a potential source for the isolation of cellulolytic bacteria. This research aims to isolate cellulolytic bacteria that function as decomposers in Baglog compost. Oyster mushroom baglog compost was used as a substrate, and bacteria were isolated using Nutrient Agar (NA) media and Carboxymethyl Cellulose (CMC) media. Qualitative testing method was done with congo red test. The results of the study successfully characterized 3 (three) potential cellulolytic bacterial isolates characterized by a cellulolytic index of more than 1 (1-1.75) and have the following characteristics: one isolate is milky white with a large round shape, one isolate is white with a large choppy shape, and one isolate is yellow with a medium round shape. These findings indicate that the three isolates have potential as cellulose decomposers and can be utilized in organic waste treatment applications or compost production.